Prevalence and risk factors for stroke in a population of Southern Brazil - Leslie Copstein; Jefferson Gomes Fernandes; Gisele Alsina Nader Bastos (Arquivos de Neuro-Psiquiatria)
Stroke is the leading cause of death in many countries of Latin America. Population studies are necessary in this region. Objectives: To evaluate the prevalence of stroke and its risk factors in a population of vulnerable communities of southern Brazil. Methods: Population-based crosssectional study with systematic sampling. Individuals aged 20 and over were included (n=3,391). Individuals with previous diagnosis of stroke or identified by a validate stroke questionnaire were compared with those without stroke in many variables. Results: 285 individuals (8.4%) had previous stroke. The group without stroke showed greater average of years of study than the group with stroke (p≪0.001). Multivariable analysis identified as risk factors for stroke (p≪0.05): age from 40 to 59, age from 60 to 79, widowhood, present smoking, previous smoking, hypertension and ischemic heart disease. Conclusion: The findings in this population indicate the need of preventive cost-effective public health policies in Brazil.